1995
DOI: 10.1084/jem.182.5.1537
|View full text |Cite
|
Sign up to set email alerts
|

A major house dust mite allergen disrupts the immunoglobulin E network by selectively cleaving CD23: innate protection by antiproteases.

Abstract: SumlTlaryAsthma is a chronic life-threatening disease of worldwide importance. Although allergic asthma and related atopic conditions correlate strongly with immune sensitization to house dust mites, it is unclear why antigens from mites provoke such powerful allergic immune responses. We have characterized the protease activity of Der p I, the group I protease allergen of the house dust mite Dermatophagoides pteronyssinus, and here report that it cleaves the low-affinity immunoglobulin (Ig) E Fc receptor (CD2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
189
0
6

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(198 citation statements)
references
References 50 publications
3
189
0
6
Order By: Relevance
“…29) and the IL-2R␣ chain (30), and by modifying the balance between IFN-␥ and IL-4 (66,67). Furthermore, the proteolytic activity of Der P I enhances titers of IgE specific for the protease (68) and bystander Ags such as OVA (69).…”
Section: Discussionmentioning
confidence: 99%
“…29) and the IL-2R␣ chain (30), and by modifying the balance between IFN-␥ and IL-4 (66,67). Furthermore, the proteolytic activity of Der P I enhances titers of IgE specific for the protease (68) and bystander Ags such as OVA (69).…”
Section: Discussionmentioning
confidence: 99%
“…Cysteine protease activity of our preparations of rDer p 1 and rDer f 1 also crucially commits to the sensitization process in mice (37). Although Phillips et al (60) reported that Der p 1 stimulated purified human basophils to release IL-4, whether its cysteine protease activity is responsible for the basophil activation is unknown because their Der p 1 preparation also contained serine proteases other than Der p 1 (28,61). Whether the rDer f 1 and rDer p 1, which show cysteine protease activity but no serine protease activity (15), could stimulate basophils to produce Th2-inducing cytokines should be addressed in a future study.…”
Section: Discussionmentioning
confidence: 99%
“…15 de cisteína-proteasa como la papaína de la papaya (Carica papaya) y la bromelaína extraida de la piña (Ananas comosus) se les han demostrado propiedades alergénicas [2-51. Al Der p 1 también se le ha sugerido alguna función digestiva debido a su localización en la región gastrointestinal del ácaro y su concentración alta (0,l-0,2 nglpartícula) en la partícula fecal del ácaro (6, 7).…”
Section: %unclassified
“…Además, por su actividad enzimática, Der p 1 separa al CD23 de la membrana de los linfocitos B, alterando así la regulación de la producción de IgE (15). Los anteriores hallazgos parecen apoyar la idea de que la actividad de cisteína-proteasa de Der p 1 influya también en la patogénesis del asma alérgica.…”
Section: Cm#randabkanr Porcinounclassified